'The miskeet tree doesn't belong here': shifting land values and the politics of belonging in Um Doum, central Sudan. Issue 1 (2nd January 2018) - Elamin, Nisrin
Abstract : The new-yet-old phenomenon of 'land grabbing' is often characterized in media and NGO reports as an unstoppable tidal wave hitting the African continent. Yet, as Anna Tsing reminds us, global power rarely operates without friction (2005). From the negotiation of deals that give investors access to land, to its transformation for use in large-scale agribusiness or mining operations, the process of 'grabbing land' is rarely unilinear and always historically situated. While some land investments materialize, others run into crisis. In April of 2013, a deal was struck between government elites and a Saudi businessman over customary land in Um Doum – a peri-urban community in central Sudan – that had been utilized by local families for generations. Community members immediately mobilized against the deal using civil disobedience tactics and media advocacy, forcing government officials to reverse the land deal and to initiate negotiations aimed at locally redistributing the land through registration and titling. Despite the apparent success of this resistance to a large-scale land deal, this article argues that the subsequent programme of land titling nevertheless represented the extension of state control over land tenure and generated profound change in gendered and ethnic social relations and land values. As such, the Um Doum negotiations served to restructure, rather than reverse, the process of land dispossession. It concludes that even when large-scale land deals are renegotiated in favour of those dispossessed, it is important to consider the ways in which 'negotiability' in land rights (Peters, 2004) can benefit elites and exacerbate existing social divisions by intensifying forms of inequality in land access.